Islam - Science Integration Approach in Developing Chemistry Individualized Education Program (IEP) for Students with Disabilities - Jamil Suprihatiningrum (Intelektual Pustaka Media Utama, 2017)
The paper is based on a research which tries to explore, explain and describe Islam - science integration approach to develop an Individualized Education Program (IEP) for students with disabilities in chemistry lesson. As a qualitative case study, this paper is aimed at investigating how Islam - science integration approach can be underpinned for developing the IEP for Chemistry. Participants were recruited purposively and data were collected by interviews; documents’ analysis; and experts’ assessment (i.e. material experts, inclusive education experts, media experts, chemistry teachers and support teachers), then analyzed using content-analysis. The result shows Islam - science integration approach can be a foundation to develop the chemistry IEP by seeking support for the verses of the Qur'an and corresponding hadiths. Even although almost all the subject matter in chemistry can be integrated with Islamic values, this study only developed two contents, namely Periodic System of Elements and Reaction Rate.